The impact of child migration on the health and well‐being of parents left behind. (1st February 2022) - Bridges, Sarah; Liu, Lefan
Abstract: This paper uses data from the China Health and Retirement Survey to estimate the causal effect child out‐migration has on the health of parents in China. For rural parents, we show that after controlling for self‐selection, child out‐migration has a detrimental effect not only on subjective well‐being and mental health but also on cognitive function and physical health when measured using a series of clinical tests and health biomarkers. In contrast, for urban parents, only a few health effects are significant, and those that are tend to be positive. In terms of the mechanism through which migration affects parental health, we find that it is differences in the level of physical support that parents require that is central to explaining many of the health effects we observe. For those who require little physical support, the income effect helps to mitigate the negative effects associated with child out‐migration, while for more vulnerable groups of parents, the economic benefits of migration are currently no substitute for the loss of informal support networks when a child migrates.